Sistem Kendali Penghindar Rintangan Pada Quadrotor Menggunakan Konsep Linear Quadratic - Ariesa Budi Zakaria; Andi Dharmawan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
Quadrotor is one of UAV (Unmanned Aerial Vehicle) rotary wing aircraft type. Quadrotor has been widely used for various needs to military or civilian. Quadrotor can be operated manually by remote or autonomously. One of the difficulties of quadrotor operations is to avoid the obstacles before autonomous flying towards destination point. Therefore, an obstacle avoidance control system is required on quadrotor systems. Linear Quadratic Regulator is a control system that produces an input value system from state value and feedback. State value is produced from translation and rotation. That input value then converted into pulse width modulation to control the speed of the brusless motor, and it's used to do obstacles avoidance manouver.This method might reduce overshoot on the system and make response time (rise time) arrived faster than other methods. The obstacle avoidance system requires small overshoot value and an appropriate response time to avoid frictions or collisions. The result of this research is the rise time to avoid obstacles that reached 4,7 second with flight speed of 0,6 m/s and turns for roll angle equal to 14,27 °, pitch equal to 13,26 °, and yaw equal to 9,87 ° while avoidance maneuvering obstacles.